2017
DOI: 10.1007/s12602-017-9270-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Probiotics Isolated from Human Milk and Colostrum

Abstract: Several studies have demonstrated a diversity of bacterial species in human milk, even in aseptically collected samples. The present study evaluated potential probiotic bacteria isolated from human milk and associated maternal variables. Milk samples were collected from 47 healthy women and cultured on selective and universal agar media under aerobic and anaerobic conditions. Bacterial isolates were counted and identified by Biotyper Matrix-Assisted Laser Desorption Ionization-Time of Flight mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 25 publications
3
77
0
1
Order By: Relevance
“…This translocation of bacteria from maternal gut to mammary gland involves complex interactions between epithelial cells, immune cells, and bacteria [12,221]. Evidence supporting the entero-mammary pathway includes the presence of bacterial communities in colostrum collected before first infant suckling [222].…”
Section: Origins Of Milk Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…This translocation of bacteria from maternal gut to mammary gland involves complex interactions between epithelial cells, immune cells, and bacteria [12,221]. Evidence supporting the entero-mammary pathway includes the presence of bacterial communities in colostrum collected before first infant suckling [222].…”
Section: Origins Of Milk Microbiomementioning
confidence: 99%
“…A number of studies have isolated potentially probiotic bacteria from human breast milk [191,222,[264][265][266][267][268]. Traditionally, species of Lactobacillus and Bifidobacterium are most commonly used as probiotics in humans and have a long history of safe use.…”
Section: Probiotic Bacteria In Breast Milkmentioning
confidence: 99%
“…This species seems to play a beneficial role in infants by inhibiting virulent pathogens and educating the innate immune system [3]. Several studies have shown that S. epidermidis is the predominant bacteria in colostrum and milk from healthy women [4][5][6][7][8][9][10] and there is a mother-to-infant transmission through breastfeeding [11]; in fact, its presence is known to be a differential trait of the fecal microbiota of breast-fed infants when compared to that of formula-fed ones [10,[12][13][14][15][16], being already present in the first meconium obtained from both term and preterm breastfed neonates [17,18]; however, coagulase-negative staphylococci (CNS) have received a marginal attention regarding their role in the early colonization of the infant gut in contrast to lactobacilli, bifidobacteria and other gut-associated strict anaerobes.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous growth in the number of reports dedicated to BM analysis confirms the potential of this fluid to provide reliable information on human exposure to different compounds. Thanks to the presence in human milk of probiotics and prebiotics, breastfeeding is nutritional and immunologically/microbiologically essential for newborn health . In cases in which breastfeeding is not possible, a new formula of substitutive products, that simulates human milk in the best feasible way, must obviously be developed.…”
Section: Bodily Systems and Related Less‐conventional Fluidsmentioning
confidence: 99%